A new species of the genus Grammacephalus Haupt (Hemiptera: Auchenorrhyncha: Cicadellidae: Deltocephalinae) from the United Arab Emirates, with a key to species of the genus known from the Arabian Peninsula - Gnezdilov, Vladimir M. (Zootaxa, 2021)
Grammacephalus albatus sp. nov. is described from Wadi Wurayah National Park in Fujairah Emirate of the United Arab Emirates. A key to five species of Grammacephalus known from the Arabian Peninsula is given. Notes on relationships of Grammacephalus Haupt, 1929 and Bampurius Dlabola, 1977 are given, with the taxonomic position of Grammacephalus genoicus Dlabola, 1984 discussed.